Thermally-driven mesopore formation and oxygen release in delithiated NCA cathode particles. Issue 20 (7th May 2019) - Besli, Münir M.; Shukla, Alpesh Khushalchand; Wei, Chenxi; Metzger, Michael; Alvarado, Judith; Boell, Julian; Nordlund, Dennis; Schneider, Gerhard; Hellstrom, Sondra; Johnston, Christina; Christensen, Jake; Doeff, Marca M.; et al.
Abstract : The structural integrity of layered Ni-rich oxide cathode materials is one of the most essential factors that critically affect the performance and reliability of lithium-ion batteries. Abstract : The structural integrity of layered Ni-rich oxide cathode materials is one of the most essential factors that critically affect the performance and reliability of lithium-ion batteries. Prolonged battery operation often involves repeated phase transitions, buildup of mechanical stresses, and could provoke thermal spikes. Such sophisticated chemo-thermo-mechanical interplay can cause performance degradation through structural disintegration of the cathode active materials (CAMs). Herein, we systematically investigate the thermal decomposition, fracture, and oxygen evolution of chemically delithiated Li0.3 Ni0.8 Co0.15 Al0.05 O2 (NCA) particles upon heating from 25 °C to 450 °C using a number of advanced X-ray and electron probes. We observed a continuous reduction of the Ni oxidation state upon heating, as well as the release of oxygen from the NCA lattice that undergoes the thermally induced phase transformations. The release of oxygen also created numerous mesopores throughout the analyzed particles, which could significantly affect the chemical and mechanical properties of the electrode. In addition, intergranular and intragranular fracturing at elevated temperatures also contribute to the degradation of the NCA cathode under these conditions. Our investigation of the mechanical integrity at elevated temperatures provides a fundamental understanding of the thermally driven chemomechanical breakdown of the NCA cathode active materials.